Myeloma Bone Disease - Roodman, G. David; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
This state-of-the-art book presents the forefront in the science and clinical management of myeloma bone disease. Assembling the work of the world's premier thought leaders, this book begins with sections on clinical presentation, imaging, and biochemical markers and then goes on to discuss radiation, surgical, and medical therapies. Specific chapters are devoted to bisphosphonates and novel therapeutic agents, such as RANKL inhibitors, Wnt signaling inhibitors, and IMiDs. The mechanisms of osteoclast activation and osteoblast suppression in multiple myeloma are also explored. Myeloma Bone Disease is a valuable resource for medical, surgical, and radiation oncologists and cancer researchers.
Clinical Presentation of Myeloma Bone Disease -- Imaging of Multiple Myeloma, Solitary Plasmacytoma, MGUS, and Other Plasma Cell Dyscrasias -- Biochemical Markers of Bone Remodeling in Multiple Myeloma -- Radiation Therapy in Multiple Myeloma -- Surgical Management of Bone Disease -- Bisphosphonates in the Treatment of Myeloma Bone Disease -- Osteonecrosis of the Jaw -- Murine Models of Myeloma Bone Disease: The Importance of Choice -- RANK Ligand Is a Therapeutic Target in Multiple Myeloma -- Osteoclast Activation in Multiple Myeloma -- Potential Role of IMiDs and Other Agents as Therapy for Myeloma Bone Disease -- Proteasome Inhibitors and the Wnt Signaling Pathway in Myeloma Bone Disease -- Mechanisms Involved in Osteoblast Suppression in Multiple Myeloma.
Keywords: Medicine; Radiotherapy; Hematology; Oncology; Medicine & Public Health; Oncology; Hematology; Radiotherapy